DIGITAL TOOLS AND HISTORICAL INQUIRY: A BIBLIOMETRIC STUDY OF DIGITAL HISTORY RESEARCH - D, Ashok Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This bibliometric study explores the evolving field of digital history, focusing on its scholarly trends, key contributors, and thematic developments. Digital history involves the study and presentation of historical narratives using digital tools and technologies to enhance interpretation, collaboration, and accessibility. The analysis uses data from the Scopus database, processed with Biblioshiny and VOSviewer software, to examine 458 documents spanning 1998–2024. Key findings include annual scientific production trends, identification of the most relevant authors, and analysis of prominent sources such as Lecture Notes in Computer Science and CEUR Workshop Proceedings. A three-field plot illustrates the relationships between sources, authors, and keywords, highlighting the interdisciplinary nature of the field. Thematic analysis using a thematic map and keyword co-occurrence network categorizes topics into foundational, emerging, niche, and motor themes, revealing methodological innovations such as text mining and data visualization. Bibliographic coupling and co-authorship analyses showcase collaborations among researchers and nations, emphasizing the global and collaborative nature of digital history. The study identifies gaps in foundational theoretical development, the limited integration of niche themes, and the underutilization of computational methodologies across subfields. Practical implications include recommendations for strategic resource allocation, curriculum development, and the creation of user-friendly digital tools for historians. Overall, this research provides a comprehensive overview of the field’s current landscape and suggests pathways for its future growth and interdisciplinary integration.